SELF EFFICACY PENCEGAHAN KOMPLIKASI HIPERTENSI DENGAN TINGKAT PENDIDIKAN MENENGAH DAN TINGGI - Kuzzairi, Kuzzairi; Fauziyah, Endang; Zaifah, Sulviatus (Jurnal Sains dan Teknologi Kesehatan, 2023)
High blood pressure is a dangerous condition that requires immediate action. Hypertension for a long time can trigger complications and is a major cause of sudden death in the world, which is always increasing every year. Deviations in hypertension control are the result of a lack of knowledge in attitude. In addition, self-efficacy for preventive abilities plays an important role in controlling hypertension. The purpose of this study was to determine the self-efficacy of preventing complications in hypertensive patients with secondary and tertiary education levels in the Gunung Sekar sub-district, Sampang district. Methods: The design of this study is descriptive cross sectional. The population and sample are all hypertension sufferers with secondary and tertiary education levels as many as 35 people with total sampling technique. Data collection in this study used a closed ended-likert scale questionnaire with a total of 5 questions and then data processing was carried out in the form of editing, scoring, coding, tabulating and interpreting the results were presented in table form and descriptive analysis. Results: Most of the hypertension sufferers with secondary education level had high self-efficacy as many as 11 respondents (65%) and almost all respondents with hypertension with higher education level also had high self-efficacy as many as 17 respondents (94%). Conclusion: Patients with hypertension with secondary and higher education levels in the Gunung Sekar sub-district, Samapang district have high self-efficacy. It is expected for sufferers to maintain high self-efficacy to prevent complications. Keywords: Self Efficacy, Hypertension, Education Level